If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-3 + 2b) = -90 (-3 * 6 + 2b * 6) = -90 (-18 + 12b) = -90 Solving -18 + 12b = -90 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 12b = -90 + 18 Combine like terms: -18 + 18 = 0 0 + 12b = -90 + 18 12b = -90 + 18 Combine like terms: -90 + 18 = -72 12b = -72 Divide each side by '12'. b = -6 Simplifying b = -6
| V=pir^2h2/3 | | -5(-7+3x)=-70 | | x(800+x)x(100+30)= | | 625=3.14(r^2) | | -123=-3(7x-8) | | -6(x+1)-13=21+8 | | 92=-4(7a-2) | | 6(3r-2)-6=-90 | | 7x^2-14x+7=0equation | | b=2/3ac | | g(x)=3x^2-6x-2 | | 12m^2+11m-18=0 | | -129=-8(6b-1)+7 | | p^2+7p+71=0 | | x^3+17x^2-16x-6=0 | | 8w=20 | | 102=(x-12)+(x+18) | | -8x+10=-5x+4 | | 800+100+30=0 | | 7(1-7x)-5x=-371 | | 2*ln*x-ln*25=0 | | 50-3x+5=15-x | | 4(r+2.3)-9r=13.5 | | 4x+1=-2x-11 | | H=-16t+24t+4 | | 15x+7y=-9 | | -138=6(5v-7)-6v | | 15x+8y=-9 | | 21+27m=28+20m | | 4y^2+7=263 | | 170=-8(8p+3)+2 | | 3.8q-4.5-5.9q=-1.1q-4.5 |